2006
DOI: 10.1002/anie.200602553
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Benzotetra‐ and Benzopentacyclic Compounds through Intramolecular [2+3] Photocycloaddition of Alkenes to Naphthalene

Abstract: Rings from light: Irradiation of acetonitrile solutions containing 1‐cyano‐2‐(4‐pentenyl)naphthalene derivatives afforded benzotetra‐ and benzopentacyclic compounds with tri‐ and tetraquinane skeletons in high yields, through intramolecular [2+3] photocycloaddition of the alkene at the 2,4‐positions of the cyanonaphthalene (see scheme; n=1, 2). The structures of these adducts were confirmed by their spectral properties and by X‐ray crystallographic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…An intramolecular reaction with a naphthalene moiety linked to an alkene gave mixtures of ortho and meta cycloadducts, but prolonging irradiation times reduced the amount of ortho in favor of meta compound: the ortho reaction is clearly reversible (Scheme 91). 176 The more complex structures 367 were obtained in good yields (74% and 85% respectively). Also, reaction with an oxygen within the tether gave moderate to excellent yields of the meta adduct (up to 84%); however, for 364, 29% of the ortho adduct was also observed.…”
Section: Meta Cycloaddition With Chiral Inductionmentioning
confidence: 99%
“…An intramolecular reaction with a naphthalene moiety linked to an alkene gave mixtures of ortho and meta cycloadducts, but prolonging irradiation times reduced the amount of ortho in favor of meta compound: the ortho reaction is clearly reversible (Scheme 91). 176 The more complex structures 367 were obtained in good yields (74% and 85% respectively). Also, reaction with an oxygen within the tether gave moderate to excellent yields of the meta adduct (up to 84%); however, for 364, 29% of the ortho adduct was also observed.…”
Section: Meta Cycloaddition With Chiral Inductionmentioning
confidence: 99%
“…Photolysis of a tethered arene–alkene system, leading to efficient [4 + 2], [3 + 2], and/or [2 + 2] cyclization, has attracted much mechanistic and synthetic interest as a tool for constructing complex polycyclic carbon frameworks . Photoreaction of an intramolecular donor (D)–acceptor (A) system has also been investigated extensively to reveal that the formation of folded or compact exciplex (CEX) plays a vital role in determining the fate of an excited D–A pair. In theory, an exciplex is described by a linear combination of the wave functions of locally excited (LE) and radical ion pair (IP) states, the relative contribution of which varies with the redox properties of D and A.…”
mentioning
confidence: 99%
“…Interestingly, the related linear-type benzotriquinane derivative 3a′, which could have been generated by photoinduced intramolecular addition of the alkyne moiety to the 1-cyanonaphthalene ring, was not formed in this process. 14 In a similar manner, irradiation of various phenyl rings and chain substituted analogs 1b-g were observed to produce the corresponding benzocyclooctatetraenes 2b-g and benzotriquinanes 3b-g (Table 1). Photoreactions of 1f-g, in which the two reaction centers are connected by an ether linkage, occur much more efficiently than those of 1a-e.…”
mentioning
confidence: 78%
“…12 Recently, intermolecular [2π + 2π] photocycloadditions of phenylethyne and diphenylethyne across the 1,2-positions of N-methyl-2,3-and 1,8naphthaledicarboximides were investigated by Liu et al 13 We have recently reported the results of studies probing intramolecular photocycloadditions of cyclic and acyclic alkenes to 1-cyanonaphthalene that produce [3 + 2] photocycloadducts, which have linear-type benzotriquinane skeletons. 14 Below, we describe the results of an effort aimed at investigating the intramolecular photocycloaddition reactions of phenylethyne to 1-cyanonaphthalene, which give rise to benzotriquinanes through routes involving the initial formation of benzocyclooctatetraenes.…”
mentioning
confidence: 99%